NANODIAMONDS FOR FLUORESCENT CELL AND SENSOR NANOTECHNOLOGIES - V. I. Nazarenko; O. P. Demchenko (Biotechnologia Acta, 2013)
This review addresses the analysis of properties and applications of fluorescent nanodiamonds. They are carbon nanostructures with atomic arrangement of a diamond and carry all its properties, including record — high density, rigidity and refraction index. They are of almost spherical shape, and their small size (~4–10 nm) creates substantial surface area that can be used for absorption of different compounds including drugs. Their surface is formed by different chemical groups (hydroxyls, carboxyls, etc.) exhibits also chemical reactivity that allows different types of modifications. This opens innumerable possibilities for constructing different functional nanomaterials. The technologies have been developed for making these nanodiamonds fluorescent. Particularly, these properties are achieved by radioactive treatment with the formation of N–V impurities. These particles absorb and emit light in convenient for observation visible range of spectrum. They do not photobleach, which is very attractive for fluorescent microscopy of the cell. And, finally, these nanoparticles do not display toxicity on the cellular or whole — body level, and because of their biocompatibility they can be used in vivo as contrast agents and drug carriers. It is expected that future biotechnological applications of these nanoparticles will be connected with the creation of nanocomposites that combine multiple useful functions.